1996
DOI: 10.1093/infdis/173.6.1379
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Resistance to a Human Immunodeficiency Virus Type 1 Proteinase Inhibitor: Mutations, Kinetics, and Frequencies

Abstract: Resistance to saquinavir (Ro 31-8959), an inhibitor of human immunodeficiency virus type I proteinase, was studied in peripheral blood mononuclear cell-derived proviral DNA from patients undergoing prolonged treatment. A Leu90-->Met exchange was the predominant resistance mutation in vivo; Gly48-->Val or doubly mutant virus was rarely observed. After 8-12 months of treatment with saquinavir alone (600 mg, 3 times/day) or in combination with zidovudine (200 mg, 3 times/day), approximately 45% of all patients ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
105
0
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(114 citation statements)
references
References 33 publications
8
105
0
1
Order By: Relevance
“…Los beneficios de la terapia antiviral pueden verse comprometidos cuando aparecen ciertos factores, como defectos de la inmunidad del huésped, alta capacidad del virus para desarrollar resistencia a los fármacos (13,(17)(18)(19)(20)(21), y pobre cumplimiento del tratamiento. A esto se suma el alto costo y el bajo acceso a los medicamentos en los países en vía de desarrollo, así como la alta toxicidad de los mismos (22,23).…”
unclassified
“…Los beneficios de la terapia antiviral pueden verse comprometidos cuando aparecen ciertos factores, como defectos de la inmunidad del huésped, alta capacidad del virus para desarrollar resistencia a los fármacos (13,(17)(18)(19)(20)(21), y pobre cumplimiento del tratamiento. A esto se suma el alto costo y el bajo acceso a los medicamentos en los países en vía de desarrollo, así como la alta toxicidad de los mismos (22,23).…”
unclassified
“…However, in clinical practice, virologic failure of protease inhibitor-containing therapy occurs in a significant fraction of the treated population (19,22,42,46,52,70). Virologic failure of protease inhibitor treatment is often due to the selection of HIV-1 strains with mutations in the pro gene, which encodes the viral protease (PR), and in specific protease cleavage sites encoded in the gag gene that collectively confer reduced drug susceptibility to the harboring strain (11,12,28,36,43,47,72).The resistance mutations are hypothesized to be largely preexisting, generated by the highly error-prone and rapid replication of HIV-1 in large virus populations (5, 10, 57). However, in PI-naïve subjects, some critical resistance mutations cannot be detected or can only be detected at very low levels, suggesting that these mutations may confer a selective disadvantage relative to wild-type HIV-1 strains (3,18,25,32,34,63).…”
mentioning
confidence: 99%
“…4,10,11,13 This is essential because all PIs may engender early HIV resistance after even a week of missed medication, irregular use, or incomplete doses. [14][15][16] Furthermore, full or partial cross-resistance exists among the PIs; hence, inappropriate use of one PI may limit future therapeutic options. 3,4,10,11,[14][15][16] Although adherence is an important consideration in prescribing PIs, there are concerns that it has the potential of being used as a justification for disparities in prescribing practices for patients with HIV/AIDS.…”
mentioning
confidence: 99%
“…[14][15][16] Furthermore, full or partial cross-resistance exists among the PIs; hence, inappropriate use of one PI may limit future therapeutic options. 3,4,10,11,[14][15][16] Although adherence is an important consideration in prescribing PIs, there are concerns that it has the potential of being used as a justification for disparities in prescribing practices for patients with HIV/AIDS. It has been observed that some providers judge patients as less likely to be adherent if they are nonwhite, less educated, impoverished, or former injection drug users, 13 even though the literature suggests that none of these demographic characteristics has had a consistent association with medication adherence.…”
mentioning
confidence: 99%